Biosensing the Presence of Metal Nanoparticles by Spectrally- and Time-Resolved Endogenous Fluorescence in Water Moss Fontinalis antipyretica - Marcek Chorvatova, Alzbeta; Uherek, Martin; Chorvat, Dusan (Frontiers in Physics, 2021)
Pollution by heavy metals represents a significant environmental burden. We employed confocal microscopy with spectral detection and fluorescence lifetime imaging (FLIM) to evaluate the effect of nanoparticles (NPs) from various metals (Zinc, Nickel, Cobalt, Copper) on endogenous fluorescence of Fontinalis antipyretica moss. Short term (3-5 day) exposure to NPs, designed and fabricated by direct synthesis using femtosecond laser ablation in water, was studied. The green flavonoid and/or lignin endogenous fluorescence peaking between 500-560 nm was found increased by Zn and significantly reduced by Cu. The overall red chlorophyll fluorescence intensity with maximum at 680 nm remained largely unchanged after exposure to Ni and Zn, but was decreased in the presence of Co and completely abolished by Cu. All NPs but Zn induced changes in the fluorescence lifetimes, demonstrating increased sensitivity of this parameter to environmental pollution. Gathered data indicate fast responsiveness of the endogenous fluorescence in the Fontinalis antipyretica moss to the presence of heavy metals that can thus potentially serve as a biosensing tool for monitoring environmental pollution in the moss natural environment..